Microcutting Redox Profile and Anatomy in Eucalyptus spp. With Distinct Adventitious Rooting Competence - Vilasboa, Johnatan; da Costa, Cibele Tesser; Ransan, Leonardo Girardi; Mariath, Jorge Ernesto de Araújo; Fett-Neto, Arthur Germano (Frontiers in Plant Science, 2021)
Adventitious root (AR) development takes place in an intricate cellular environment. Reactive oxygen species (ROS) and antioxidant defenses, triggered by wounding in cuttings, can modulate this process. A comparative assessment of biochemical and anatomical parameters at critical rooting stages in hard- (Eucalyptus globulus Labill.) and easy- (Eucalyptus grandis W.Hill ex Maiden) to-root species was carried out. Microcuttings from seedlings were inoculated in auxin-free AR induction medium and, after 96 h, transferred to AR formation medium for a period of 24 h. Samples were collected upon excision (Texc) and at the 5th day post excision (Tform). Delayed xylem development, with less lignification, was recorded in E. globulus, when compared to E. grandis, suggesting lower activity of the cambium layer, an important site for AR development. Superoxide was more densely present around the vascular cylinder at both sampled times, and in greater quantity in E. globulus than E. grandis, declining with time in the former. Hydrogen peroxide was localized primarily along cell walls, more intensely in the primary xylem and phloem, and increased significantly at Tform in E. globulus. Ascorbate peroxidase (APX), superoxide dismutase (SOD), and catalase (CAT) activities were generally higher in E. grandis and varied as a function of time in E. globulus. Soluble guaiacol peroxidase (GPRX) activity increased from Texc to Tform in both species, whereas cell wall-bound GPRX activity increased with time in E. grandis, surpassing E. globulus. Flavonoid content increased with time in E. grandis and was higher than E. globulus at Tform. Principal component analysis showed that species- and time-derived differences contributed to almost 80% of the variance. Overall, data indicate that E. grandis shows higher cambium activity and tighter modulation of redox conditions than E. globulus. These features may influence ROS-based signaling and phytohormone homeostasis of cuttings, thereby impacting on AR development. Besides being players in the realm of AR developmental differences, the specific features herein identified could become potential tools for early clone selection and AR modulation aiming at improved clonal propagation of this forest crop.